Method for calculating cyclic load induced 1D and PVD unit cell consolidation deformations. (August 2021) - Chai, Jin-chun; Fu, Hong-tao; Wang, Jun; Shen, Shui-Long; Ding, Wenqi
Abstract: Consolidation deformation induced by low frequency cyclic loads was investigated by finite element analysis (FEA) and some available test data. Both one-dimensional (1D) consolidation and the consolidation of a prefabricated vertical drain (PVD) unit cell were considered. With theoretical reasoning and using the results of FEA, it has been established that the amount and the rate of consolidation deformation induced by a continuous cyclic load with a maximum load increment of q, can be calculated using the consolidation result of a static load with a magnitude of q /2. Providing the compression increment ( ΔS ) near the drainage boundary where the effective stress increment is larger than q /2 is taking into account. The magnitude of ΔS is cyclic load frequency dependent and a method for evaluating it has been proposed. Further, it has been proposed that during the cyclic loading period, the creep deformation induced by sustained static load on a soil layer should be included into the total deformation. The proposed method was applied to two 1D and one PVD unit cell laboratory tests of cyclic load induced consolidations. Good agreement between the measured and the calculated settlement – time curves was obtained.